2012
DOI: 10.2478/v10172-012-0096-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behaviour of ultrafine grained Al-Mg alloys obtained by different processing routes

Abstract: The subject of the study were microstructure and mechanical properties of two commercial 5xxx aluminium alloys obtained by Plastic Consolidation (PC) of nanopowders and Hydrostatic extrusion (HE). It has been observed that HE samples exhibit a higher strength whereas PC samples higher ductility. The two types of samples also differ in the type and intensity of serrations on stress-strain curves. The microstructures of samples processed were found to differ significantly in terms of size and shape of grains, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Considerable strain is made using workpiece SPD technologies such as high-pressure torsion (HPT), equal channel angular pressing (ECAP) [8], friction stir processing (FSP) [9], twist extrusion (TE) [10], and others. Classical extrusion and hydro extrusion methods are also applied, and they have demonstrated effectiveness in the consolidation and grain refinement of Al alloy powder composites [11]. The authors of [11] showed that AA5xxx alloys can be efficiently strengthened up to a flow stress exceeding 450 MPa by both the hydro extrusion of solid preforms and extrusion compaction of nanopowders, and both obtained composites exhibited tensile elongation values greater than 10%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerable strain is made using workpiece SPD technologies such as high-pressure torsion (HPT), equal channel angular pressing (ECAP) [8], friction stir processing (FSP) [9], twist extrusion (TE) [10], and others. Classical extrusion and hydro extrusion methods are also applied, and they have demonstrated effectiveness in the consolidation and grain refinement of Al alloy powder composites [11]. The authors of [11] showed that AA5xxx alloys can be efficiently strengthened up to a flow stress exceeding 450 MPa by both the hydro extrusion of solid preforms and extrusion compaction of nanopowders, and both obtained composites exhibited tensile elongation values greater than 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Classical extrusion and hydro extrusion methods are also applied, and they have demonstrated effectiveness in the consolidation and grain refinement of Al alloy powder composites [11]. The authors of [11] showed that AA5xxx alloys can be efficiently strengthened up to a flow stress exceeding 450 MPa by both the hydro extrusion of solid preforms and extrusion compaction of nanopowders, and both obtained composites exhibited tensile elongation values greater than 10%. It is important to note the excellent mechanical properties of severely deformed alloys, which are based on grain size reduction and strain hardening.…”
Section: Introductionmentioning
confidence: 99%
“…The extrusion pressure is affected by geometrical factors such as extrusion ratio and die angle, the flow stress of the material, and the friction forces between die and billet [6]. At present, most of the available publications are focused on the effect of SPD on polycrystalline materials [7][8][9][10]. The authors of the present paper were concerned with investigating changes in single crystals and polycrystalline material subjected to SPD realized by HE.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, aluminium alloys of 5xxx series are known to be weldable and corrosion resistant, however due to lack of the precipitation strengthening mechanism, poses only moderate strength. It is known that susceptibility of Al-Mg system to precipitation hardening is negligible, thus considering significant improvement of mechanical properties of Al-Mg alloys research interest should be focused on hardening mechanisms based on: solid solution, deformation and grain size strengthening [1].…”
Section: Introductionmentioning
confidence: 99%